"CHACHAPOYAS" AND "PURUM": ANCESTRAL IDENTITY AND SYMBOLIZATION OF A LATE PERIOD SOCIETY IN THE DEPARTMENT OF AMAZONAS - Ruíz Barcellos, Jorge Luis (2011)
“In this country men and women different from many parts of the Incas wear clothes of wool on their heads have their llauto dedicated to livestock, produce very fine upholstery; have Cuchaycuella as God and belief in the stars chuquechinchay or image of a tiger, lion or cat, “and described the Chachapoyas early historians (Cieza de León 1553; Albornoz 1570; Garciliso de la Vega 1609; Calancha 1638) - Today, largely persists in all the stories and the traditional life Utcubambinos of Jalquinos and hardening. Some historical studies report that the administration would have identified those Cusqueña this way the local people, and even between the seventeenth and eighteenth centuries would have records of more population groups with names, but archeology has failed not only to identify materially the diversity of groups. Chachapoyas is still understood as a territorial and cultural space that would include more than 90 thousand km2, where they developed “cities” “population centers” places of religious and infrastructure and connectivity that today, many still their remains are hidden or silent in the current departments of Amazonas, San Martín and La Libertad, and even in areas adjacent to the current Huánuco. Due to the nature historiographical only have until today known as the Chachapoyas that, we have decided to revisit the issue from observations from other perspectives, which have not been very well supported and deepened. A structural analysis of ethnolinguistic and symbolization that permanently possess the Andean photographs in this case located in the Andean and Amazonian normal contexts allow us to observe new senses of identity, but also symbolizing that should change the way we understand the identity of Chachapoyas (s) in the north Andean and Amazonian context.